PENGARUH BAHAN ORGANIK (Puerariajavanica) DAN FOSFAT ALAM TERHADAP PERTUMBUHAN DAN SERAPAN P TANAMAN JAGUNG (Zea mays) PADA ANDISOL PASIR SARONGGE - Sri Djuniwati; Arief Hartono; Lilik Tri Indriyati (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2003)
Phosphor (P) is the second esensial element after nitrogen which is needed by plants, however, its avaiiability is a problem in vulcanic ash soils such as Andisol. The objective of the research was to study the effect of organic matter (Pueraria javanica) and rock phosphate to the growth and P-uptake of corn plant in Andisol Pasir Sarongge. The experiment was conducted in the greenhouse of Soil Department, Faculty of Agriculture, Bogor Agriculture University. The design of the experiment was completely randomized design with two factors and three replications. The first factor was the rates of organic matter (0, 2.5%, and 5%) and the second factor was the rates of rock phosphate (0, 40 mg Plkg, and 80 mg Plkg), therefore there were 27 of treatments of experiment. Three kilogram of soil samples were put in the plastic bag and mixed with combination of organic matter and rock phosphate based on the treatments and then incubatedfor 4 week periods. After incubation, five seeds of corn were planted, and then were selected and left three plants after one week period. The soil moisture was maintained to water holding capacity. The results of the study showed that after 4 weeks of planting (4WAP), addition of organic matter increased plant height, dry matter and P- uptake of corn plant. However, the effect between the rate of 2.5% and 5% of organic matter to those variables above were not significantly different. The increased of plant height (4WAP), dry matter, and P-uptake due to addition of organic matter were in the range of 32-41%, 68-105%, and 84-92%, respectively. Meanwhile. addition of rock phosphate. and combination of organic matter and rock phosphate did not affect those variables. Keywords: Andisol, organic matter, Puerariajavanifa, P-uptake, rock phosphate